The The Long- and Short-Run Effects of GDP, Labor Force, and Industrial Growth on Unemployment in Indonesia - Basuki, Agus Tri (Balance : Jurnal Akuntansi dan Manajemen, 2024)
This study investigates the impact of GDP per capita, labor force participation (LABOR), and manufacturing value added (MVA) on unemployment (UE) in Indonesia using annual data from the World Development Indicators (WDI) for the period 1990–2023. Employing an Error Correction Model (ECM), the analysis distinguishes between short-term dynamics and long-term relationships among the variables. The findings reveal that, in the long run, GDP per capita, LABOR, and MVA significantly influence unemployment. In the short run, however, only GDP per capita and MVA are found to have a statistically significant effect. The estimated Error Correction Term (ECT) of -0.505068 indicates a moderate speed of adjustment towards long-term equilibrium following short-term shocks.Policy Implications: The results suggest that promoting inclusive economic growth and enhancing the industrial sector's contribution to GDP can play a crucial role in reducing unemployment in Indonesia. Moreover, optimizing labor force participation through targeted employment and education policies could strengthen the long-term resilience of the labor market.Research Contribution: This study contributes to the existing body of literature by offering a comprehensive long-term and short-term perspective on the macroeconomic determinants of unemployment in a major emerging economy. By using up-to-date data and applying the ECM framework, the research provides valuable insights for policymakers seeking evidence-based strategies to address labor market challenges in developing countries.